PENGARUH VARIASI LATIHAN DRILL DAN LATIHAN FIRST TOUCH UNTUK MENINGKATKAN PASSING DAN CONTROLING DALAM SEPAK BOLA PADA PEMAIN USIA 10-12 TAHUN DI SSB SAUSU RAYA - Nasar Ashari; Didik Purwanto; addrian Bulu Baan; Humaedi; Gunawan (JURNAL ILMU KEOLAHRAGAAN, 2026)
This study aimed to examine the effects of first touch training variations, namely first touch two player drill, first touch triangle drill, and first touch on the move, on improving passing and ball controlling skills of 10–12-year-old players at SSB Sausu Raya. The research employed an experimental method using a quasi-experimental design with a three groups pretest–posttest design. The sample consisted of 30 players divided into three experimental groups, each comprising 10 players. Data were collected using passing and stopping skill tests. Data analysis included normality testing, homogeneity testing, paired sample t-test, and independent sample t-test at a significance level of 0.05.The results revealed that all first touch training variations had a significant effect on improving passing and ball controlling skills, as indicated by significance values of 0.00 < 0.05 in all experimental groups. However, the independent sample t-test results indicated no significant differences among the three training variations. It can be concluded that first touch two player drill, triangle drill, and first touch on the move are equally effective in enhancing passing and ball controlling skills of 10–12-year-old soccer players. This study recommends the flexible and integrated application of first touch training variations in youth soccer development programs.